Interrater Reliability among Endoscopists: Diagnosis of Laryngopharyngeal Reflux Based on the Reflux Finding Score Determined by Upper Endoscopy - Seok Won Lee; Chang Seok Bang; Yeon Soo Kim; Gwang Ho Baik; Dong Kyu Kim; Young Don Kim; Koon Hee Han; Sang Jin Lee; Jong Kyu Park; Hyun Il Seo; Sung Chul Park; Sang Hyuk Lee; et al. (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Background/Aims: Laryngopharyngeal reflux (LPR) is an extraesophageal manifestation of gastroesophageal reflux disease. Endoscopic assessment of LPR is needed for convenient diagnosis and documentation of treatment efficacy. The aim of this study was to investigate the interrater reliability of LPR among endoscopists based on endoscopic laryngeal images. Materials and Methods: Nineteen endoscopists participated in this study. Before the test, they completed an intensive education program by an otorhinolaryngologist on the reflux finding score (RFS), which is a validated laryngoscopic assessment of LPR. A total of 100 endoscopic laryngeal images were used for 3 tests of RFS. Cohen’s and Fleiss’ kappa coefficients were used to determine the degree of interrater agreement in the diagnosis of LPR. Results: In the first test, the mean of Cohen’s kappa coefficients for LPR diagnosis between the otorhinolaryngologist and each of the 19 endoscopists was 0.3. In the second test, after additional education, the mean kappa value was 0.32. Fleiss’ kappa coefficients for diagnosis of LPR among the 19 endoscopists in the first and second tests were 0.30 and 0.26, respectively. Conclusions: A short-term education program for endoscopists did not result in an improvement of accuracy in the diagnosis of LPR. Further studies using advanced educational programs for endoscopists are required.